The Implementation of Self-Regulated Learning in Reading Comprehension Class of a State Junior High School in Surabaya - Erlin Novianti (Retain: Journal of Research in English Language Teaching, 2024)
Reading requires the most self-regulation because it challenges students to coordinate different types of information. This research aims to describe implementation Self-Regulated Learning in students' reading comprehension and perception as well as in the Reading class. The sample population for this research was 32 grade 8 students at SMPN 6 Surabaya. Data regarding student autonomy are collected through well-validated questionnaires and interviews to collect data. The research findings revealed that 8th grade students showing a high level of awareness of student autonomy, the dominant strategy used by junior high school students in the reading comprehension class is metacognitive self-regulation. This shows that students with a higher level of autonomy tend to show better English language skills competence. The result is the higher the awareness of Self Regulated Learning that students have, the higher the self-regulation of the learning strategies they use, and the higher the implementation of SRL learning carried out by students, the higher the student achievement results. Educators and policy makers can use these findings to develop strategies and interventions that promote learning autonomy and facilitate improved English learning results. Further research is recommended to explore this further factors that can influence student autonomy and relationships with English language competency in reading comprehension.